2007
DOI: 10.1021/jf062020b
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Antitumor Activity of Momilactone B from Rice Hulls

Abstract: The cytotoxic and antitumor activity of methanolic extract of rice hulls (MERH) were evaluated by the MTT-dye reduction assay against human colon cancer cells and the colonic aberrant crypt foci (ACF) assay in 1,2-dimethylhydrazine (DMH)-injected F344 male rats, respectively. MERH was found to be highly cytotoxic, with IC50 values of 0.5 microg/mL in vitro. Forty weeks of MERH supplementation (50 mg/kg of body weight/day) reduced colonic pre-neoplastic ACF formation by 35% (p < 0.01). An active compound, momil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 18 publications
2
60
0
Order By: Relevance
“…In previous research, the quantification of momilactones A and B was reported using HPLC (Lee et al 1999;Shimura et al 2007;Lee et al 2002;Kong et al 2004;Kim et al 2007;Kato-Noguchi and Ota 2013). However, their contents can also be determined by GC-MS, which have been noted in in several reports (Matsuyama 1983;Fukuta et al 2007;Kodama et al 1988), as well as in this study, using standard momilactones A and B to compare their retention times, mass spectra, and fragments.…”
Section: Contents Of Momilactones a And Bsupporting
confidence: 51%
See 1 more Smart Citation
“…In previous research, the quantification of momilactones A and B was reported using HPLC (Lee et al 1999;Shimura et al 2007;Lee et al 2002;Kong et al 2004;Kim et al 2007;Kato-Noguchi and Ota 2013). However, their contents can also be determined by GC-MS, which have been noted in in several reports (Matsuyama 1983;Fukuta et al 2007;Kodama et al 1988), as well as in this study, using standard momilactones A and B to compare their retention times, mass spectra, and fragments.…”
Section: Contents Of Momilactones a And Bsupporting
confidence: 51%
“…Since momilactones A and B were first discovered by Kato et al (1973), major research has been conducted on the two compounds concentrated on plant growth and pathogen (Fukuta et al 2007;Okada et al 2007;Hasegawa et al 2010), and antioxidant capacity (Fukuta et al 2007), cytotoxic and antitumor activity (Kim et al 2007), whereas other biological activities of momilactones A and B have remained unknown. This study is the first to demonstrate that momilactones A and B correlated to the tolerance of drought and salinity in much stronger levels than the weed tolerance in rice.…”
Section: Correlation Coefficientsmentioning
confidence: 99%
“…Joung et al [72] 2008 Momilactone B (rice husk) Suppressed hypoxia-induced increases in phospho-STAT5, STAT5b, cyclin D1, and cdk4 protein levels in human breast cancer cells.…”
Section: Licheniformis)mentioning
confidence: 99%
“…Although this compound has been studied as an allelochemical of rice (14,15), several reports have revealed that momilactone B exhibits several biological activities as a potential herbicidal agent (16,17). More recently, momilactone B has been shown to be a novel potential chemotherapeutic agent to induce apoptosis in solid human tumors and blood cancer cells (18,19). However, the anticancer effects of momilactone B have not been well investigated.…”
Section: Introductionmentioning
confidence: 99%